Correction: Niche overlap across landscape variability in summer between two large herbivores using eDNA metabarcoding. - Eduard Mas-Carrió; Marcin Churski; Dries Kuijper; Luca Fumagalli (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0279672.].